Antimicrobial properties of 4-((5-(decylthio)-4-methyL-4H-1,2,4-triazole-3-yl)-methyl)morpholine - Ogloblina, M. V.; Bushueva, I. V.; Parchenko, V. V.; Martynyshyn, V. P.; Zazharskyi, V. V.; Bilan, M. V.; Kulishenko, O. M.; Бушуєва, Інна Володимирівна; Парченко, Володимир Володимирович (My University, 2023)
The study of the antimicrobial properties of 4-((5-(decylthio)-4- methyl-4H-1,2,4-triazol-3-yl)-methyl)morpholine against new strains of microorganisms is an urgent issue, which in turn can expand the list indications for the use of this compound. The drug «Vetmikoderm» is recommended for the treatment of animals with various skin diseases of fungal and microbial etiology. Thus, further studies of this compound with the aim of improving the drug are relevant and have theoretical and practical significance.
Keywords: 1,2,4-triazole derivatives; antimicrobial activity; «Vetmikoderm»; strains of the Enterobacteriaceae; Enterococcaceae; Staphylococcaceae; Pseudomonadaceae Bacillaceae families; in vitro